Auditing the Physical Activity and Parkinson Disease Literature Using the Behavioral Epidemiologic Framework. Issue 6 (21st October 2016) - Swank, Chad; Shearin, Staci; Cleveland, Samantha; Driver, Simon
Abstract: Motor and nonmotor symptoms associated with Parkinson disease place individuals at greater risk of sedentary behaviors and comorbidities. Physical activity is one modifiable means of improving health and reducing the risk of morbidity. We applied a behavioral framework to classify existing research on physical activity and Parkinson disease to describe the current evolution and inform knowledge gaps in this area. Research placed in phase 1 establishes links between physical activity and health‐related outcomes; phase 2 develops approaches to quantify physical activity behavior; phase 3 identifies factors associated with implementation of physical activity behaviors; phase 4 assesses the effectiveness of interventions to promote activity; and phase 5 disseminates evidence‐based recommendations. Peer‐reviewed literature was identified by searching PubMed, Google Scholar, and EBSCO‐host . We initially identified 287 potential articles. After further review, we excluded 109 articles, leaving 178 included articles. Of these, 75.84% were categorized into phase 1 (n = 135), 10.11% in phase 2 (n = 18), 9.55% into phase 3 (n = 17), 3.37% into phase 4 (n = 6), and 1.12% into phase 5 (n = 2). By applying the behavioral framework to the physical activity literature for people with Parkinson disease, we suggest this area of research is nascent with more than 75% of the literature in phase 1. Level of Evidence: III